Field infestation level of Zaprionus indianus and Drosophila suzukii (Diptera: Drosophilidae) in Ficus carica (Rosales: Moraceae) and Rubus idaeus (Rosales: Rosaceae) in the Northeast of Buenos Aires province - Dettler, Maria Antonela (2021)
Two exotic fruit flies species, Zaprionus indianus Gupta and Drosophila suzukii (Matsumura), were detected in Argentina in recent years. In this note, the southernmost detection of Z. indianus in Argentina and an estimation of the field infestation level caused by both drosophilid species on figs (Ficus carica L.) and raspberries (Rubus idaeus L.) are reported.